IMMIGRATION IN THE VIEW OF THE GATE GUARD OF THE STATE OF INDONESIA - Okta Tri Kurniawan; Raditya Putra Manda; Riki Dwi Kurniawan; Muhammad Alvi Syahrin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study aims to analyze the function of immigration in the security aspect, namely as a guard at the entrance to the territory of Indonesia during a pandemic. This function is of course very important considering that currently the spread of the covid 19 virus is getting out of control, one of which is because there are still many foreigners entering Indonesian territory. The research method used is descriptive with a qualitative approach by studying secondary data in the form of books, documents, and event records. The results of the study show that the actualization of the role of the immigration function during the pandemic can be seen from the aspects of immigration regulation and practices carried out by immigration checkpoints throughout Indonesia. Meanwhile, immigration checkpoints have carried out their functions as state security guards by refusing the arrival of foreigners and closing several immigration checkpoints to limit immigration traffic. There is a significant difference in law enforcement during normal times and during the pandemic, namely concessions given to foreign nationals in the form of exemption from overstay fees and deportation cannot be carried out. Deportation cannot be carried out because in general the country of origin of the foreigner also applies strict restrictions, so that for the time being many foreigners who cannot return to their country of origin are forced to live in the Rudenim.